2013
DOI: 10.1161/circep.113.000216
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Sudden Cardiac Death in a Nonischemic Dilated Cardiomyopathy Population

Abstract: Inducibility of ventricular tachycardia/ventricular fibrillation was associated with an increased likelihood of subsequent ICD activation and sudden cardiac death surrogate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 26 publications
3
32
1
1
Order By: Relevance
“…20 In line with this finding, we proved a decreased likelihood of VT recurrence in patients with NIDCM and complete VT noninducibility in comparison with patients with partial success or failure after CA. Previously, Piers et al 19 reached the same conclusion and suggested that noninducibility may be an appropriate end point in patients with NIDCM.…”
Section: Vt Noninducibility After Ca and Vt Recurrencesupporting
confidence: 83%
“…20 In line with this finding, we proved a decreased likelihood of VT recurrence in patients with NIDCM and complete VT noninducibility in comparison with patients with partial success or failure after CA. Previously, Piers et al 19 reached the same conclusion and suggested that noninducibility may be an appropriate end point in patients with NIDCM.…”
Section: Vt Noninducibility After Ca and Vt Recurrencesupporting
confidence: 83%
“…However, several previous results have demonstrated discrepancies between inducible ventricular tachyarrhythmias using an EP study and the presence of VAs during the follow‐up in patients with NICM and heart failure 26, 27, 28. Moreover, a recent study29 monitored patients with idiopathic DCM prospectively and found a similar total mortality between the patients with positive and negative inducibility of ventricular tachycardia/ventricular fibrillation (VT/VF) during the follow‐up. However, overall ICD therapies were significantly higher in patients with a positive inducibility of ventricular tachyarrhythmias.…”
Section: Classification and Evaluation Of Nicmmentioning
confidence: 99%
“…Extrastimuli were applied after a six-beat drive train with a 2-s interdrive pause. In DCM patients where no sustained ventricular tachyarrhythmia was triggered, PVS was repeated after intravenous isoproterenol administration (1-4 μg/kg/min) [2]. The presence of either sinus and/ or atrioventricular node disease was ascertained based on abnormal electrophysiological parameters [3].…”
mentioning
confidence: 99%